Analysis of food spices : identification and authentication - Nollet, Leo M. L., 1948-; Ahmad, Javed (Assistant professor); Ahamad, Javed (CRC Press, 2023)
"This book provides an overview of spices of different categories such as terpenes and terpenoids, oleoresins, alkaloids, and polyphenolics and flavonoids; and provide qualitative and quantitative guidelines for ensuring their quality and safety using modern analytical tools and techniques. The first section of the book discusses the overview, sources, and health benefits of important categories of spices such as terpenes and terpenoids (cardamom, cinnamon, clove, coriander, cumin, fennel), oleoresins (capsicum, ginger, nutmeg), alkaloids (black pepper, fenugreek), and polyphenolics and flavonoids (basil, turmeric, olive, saffron). In the second section of the book, qualitative diagnostic features of spices is covered. In the third section of the book, the role of quantitative analytical techniques such as HPLC, LC-MS, HPTLC, GC & GC-MS, capillary electrophoresis (CE), and other recent techniques in the analysis of food spices is also discussed. Each chapter concludes with a general reference section, which is a bibliographic guide to more advanced texts"-- Provided by publisher.
Keywords: Spices -- Analysis.; Spices -- Identification.; elektronické knihy; electronic books